Neglected and underutilised species (NUS): an analysis of strengths, weaknesses, opportunities and threats (SWOT) - El Bilali, Hamid; Cardone, Gianluigi; Falcis, Eleonora de; Naino Jika, Abdel Kader; Rokka, Susanna; Diawara, Ali Badara; Nouhou, Bassirou; Ghione, Andrea (2022)
Despite the growing attention to the neglected and underutilised species (NUS) as a valid instrument to promote not only sustainable agriculture and food systems but also sustainable development in rural areas, attempts to move from good intentions to effective actions have been limited. This is due, among others, to a gap in knowledge about the myriads of existing NUS and their potential. In this context, the present paper provides a comprehensive analysis of the strengths, weaknesses, opportunities and threats (SWOT) of crop NUS. Data for the SWOT analysis were retrieved through a review of the literature carried out in June 2022 on the Web of Science. Strengths relate, inter alia, to adaptability to harsh, marginal conditions, tolerance to biotic and abiotic stresses (e.g. pests and diseases, drought) and low external input requirements of NUS as well as their high medicinal and nutritional values combined with widespread culinary traditions. Weaknesses regard low productivity as well as difficult access to quality seeds, inputs, technologies and knowledge. Higher demand from consumers as well as increasing attention to sustainability and resilience in the whole agri-food system and agroecology represent opportunities for the promotion of NUS to address challenges such as food and nutrition insecurity and poverty. Climate change, biodiversity loss and genetic erosion, land and agroecosystem degradation, loss of traditional knowledge and heritage, and competition from commercial crops are among the main threats to NUS. The SWOT of NUS outlined in this work should inform evidence-based policies and strategies for the promotion of NUS, especially in developing countries. They should also guide the undertakings and actions of all stakeholders interested in the development of NUS value chains.